LSI Logic Reports Strong Q2 Revenue and Profit Growth (PR Newswire, 2005)
"Increased customer demand for LSI Logic's Storage Components and Storage Systems product offerings provided the momentum for LSI Logic to report a solid second quarter," said Abhi Talwalkar, LSI Logic president and chief executive officer. "Storage Components, comprised of Storage ASICs, Storage Standard Products and RAID Storage Adapters, set the pace for the company with a record second quarter. Our Engenio storage systems subsidiary benefited from the successful introduction of its higher-end product line. Growth in Communications reflected stronger than anticipated demand from enterprise networking customers. In Consumer, we were pleased with the revenue strength in DoMiNo(R) -based DVD-recorder and cable set- top box markets, as well as digital audio products, which was balanced by the seasonal decline in game console revenues." Safe Harbor for Forward-Looking Statements: This news release contains forward-looking statements, which include the following: projected revenues for the third quarter of 2005, projected GAAP net income for the third quarter of 2005, projected net income, excluding special items, for the third quarter of 2005, projected capital spending in the third quarter of 2005 and for the year, and expected third quarter of 2005 depreciation and software amortization. Forward-looking statements also include projections of gross margins, operating expenses, net other income / (expense), tax provisions, earnings per share and diluted share count. These forward-looking statements are based on the opinions and estimates of management at the time the statements are made and are subject to certain risks and uncertainties that could cause actual results to differ materially from those anticipated in the forward-looking statements. Factors that could cause LSI Logic's actual results to differ materially from those set forth in the forward-looking statements include, but are not limited to: fluctuations in the timing and volumes of customer demand, the company's ability to achieve revenue objectives, the company's ability to meet financial targets and failure to execute on its financial plan, the company's ability to generate positive operating cash flow, control operating expenses or drive sustained revenue growth, the company's ability to leverage technology marketplace advantages and the availability of appropriate levels of manufacturing capacity. For additional information, readers are referred to the documents filed by LSI Logic with the SEC, and specifically the risk factors set forth in the company's most recent reports on Form 10-K, 10-Q and 8-K. LSI Logic Corporation focuses on the design and production of high- performance semiconductors for Consumer, Communications and Storage applications that access, interconnect and store data, voice and video. LSI Logic engineers incorporate reusable, industry- standard intellectual property building blocks that serve as the heart of leading-edge systems. LSI Logic serves its global OEM, channel and distribution customers with standard-cell ASICs, Platform ASICs, standard products, host bus adapters, RAID controllers and software. In addition, the company supplies storage network solutions for the enterprise. LSI Logic is headquartered at 1621 Barber Lane, Milpitas, CA 95035. http://www.lsilogic.com .